Screening of Secreted Proteins of Sporisorium reilianum f. sp. zeae for Cell Death Suppression in Nicotiana benthamiana - Dutra, Deiziane; Agrawal, Nisha; Ghareeb, Hassan; Schirawski, Jan (Frontiers in Plant Science, 2020)
Sporisorium reilianum f. sp. zeae (SRZ) is a biotrophic fungus causing head smut in maize. Maize infection with SRZ leads to very little cell death suggesting the presence of cell-death suppressing effectors. Several hundred effector proteins have been predicted based on genome annotation, genome comparison and bioinformatic analysis. For only very few of these effectors, an involvement in virulence has been shown. In this work, we started to test a considerable subset of these predicted effector proteins for a possible function in suppressing cell death. We generated an expression library of 62 proteins of SRZ under the control of a strong constitutive plant promoter for delivery into plant cells via Agrobacterium tumefaciens-mediated transient transformation. Potential apoplastic effectors with high cysteine content were cloned with signal peptide while potential intracellular effectors were also cloned without signal peptide to ensure proper localization after expression in plant cells. After infiltration of Nicotiana benthamiana leaves, infiltration sites were evaluated for apparent signs of hypersensitive cell death in absence or presence of the elicitin INF1 of Phytophthora infestans. None of the tested candidates was able to induce cell death, and most were unable to suppress INF1-induced cell death. However, the screen revealed one predicted cytoplasmic effector (sr16441) of SRZ that was able to reliably suppress INF1-induced cell death when transiently expressed in N. benthamiana lacking its predicted secretion signal peptide. This way, we discovered a putative function for one new effector of SRZ.